’Virtual Soul’: The Aesthetics of the Disembodied Being: A Conceptual and Visual Analysis of an Artificial Influencer - Palomino-Flores, Paola; Berckholtz-Benavides, Klaus; Díaz-Hernández, Carlos (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
In the postdigital era, categories such as body, identity, and presence undergo a profound reconfiguration. Using the case of Aitana López, a virtual influencer created through artificial intelligence, this study explores new forms of technologically mediated existence. It analyses three key dimensions: existence as visibility, the body as an aesthetic interface devoid of lived experience, and the image as a form of ontological presence. The study also identifies a trend toward hyperreality and the aestheticization of the body, in which the artificial takes precedence over the real. The analysis follows a hermeneutic-visual approach applied to content from her Instagram profile. The visual image no longer merely represents; it acts, generates desire, interaction, and value. In this context, it becomes essential to represent the human without severing it from its embodied dimension.